KEKUATAN INFOGRAFIS DAN PERANNYA DALAM BUKU PANGAN FUNGSIONAL - Mahelingga, Dhevi (BACA: Jurnal Dokumentasi dan Informasi, 2021)
Infographic potential in bridging complex data, such as research results, has the opportunity to be used to better educate and further to empower the community, especially for issues that still have not received much attention in the community, such as functional food issues. The lack of attention is due to limited access and way to deliver functional food research results so that it is difficult to be accessed and understood by the community. This is because most of the delivery of research results is still in the form of reports, journals, or books that are less interesting, both in terms of language and appearance. In terms of appearance, infographics can be used to support the effectiveness of information delivery and the process of better understanding of the community. This study discusses infographic strength and its role in functional food books compared to simple graphical data visualization using the power of visual infographic theory in attracting attention, understanding, and sticking memories into the reader's mind. The results of the study are in the form of infographic potential in accelerating information education and opening up opportunities for effectiveness in decreasing human attention span.